Análise dos esforços globais de segunda ordem: comparativo entre processo P-Delta e o método Gama-Z - Guadagnin, Robson Marcelo (My University, 2020)
The construction industry has made great strides in recent years. Consequently, buildings have been designed with greater heights and this requires greater care in the analysis of their overall stability. The NBR 6118: 2014 mentions some parameters of this analysis, among them is the method of the P-Delta Process and the increase of the Gamma-Z coefficient. In this study, an architectural design of a building with 11 floors to be dimensioned in reinforced concrete was used. For the design, a structural calculation software was adopted where the dimensions and the spacing between the structural elements were designed to generate 6 scenarios with variations in global stability, that is, for each analysis of the structure, the structural elements were modeled for achieve variations in the Gamma-Z coefficient between 1.0 and 1.5. In these scenarios, the second order efforts on the structure by the P-delta process were found and compared to the second order efforts calculated by increasing the first order efforts using the Gamma-Z coefficient method. Afterwards, the internal efforts were calculated by the two calculation methods where the results and the analyzed variations were compared. It was found that in the scenarios where the first order efforts were increased by the Gamma-Z coefficient between 1.1 and 1.3, the internal efforts calculated were close to the complex calculation method of the P-Delta process. As for the results of using the Gamma Z coefficient greater than 1.3, the variations in internal efforts were large and situations that do not represent the reality of the structure can be generated. Therefore, the use of the Gamma Z 1.1 coefficient was the scenario that brought results closer to the P-Delta process method. Even though the calculation is simplified, the use of the Gamma Z-1.1 coefficient brings satisfactory results. [resumo fornecido pelo autor]
A indústria da construção civil apresentou grandes avanços nos últimos anos consequentemente, os edifícios têm sido projetados com maiores alturas e isso exige maior cuidado na análise da sua estabilidade global. A NBR 6118:2014 cita alguns parâmetros dessa análise, entre eles está o método do Processo P-Delta e a majoração do coeficiente Gama-Z. Neste estudo, utilizou-se um projeto arquitetônico de um edifício com 11 pavimentos a ser dimensionado em concreto armado. Para o dimensionamento, adotou-se um software de cálculo estrutural onde as dimensões e os espaçamentos entre os elementos estruturais foram projetados para gerar 6 cenários com variações na estabilidade global, ou seja, para cada análise da estrutura, modelou-se os elementos estruturais para alcançar variações no coeficiente Gama-Z entre 1,0 e 1,5. Nestes cenários, foram encontrados os esforços de segunda ordem incidentes sobre a estrutura pelo processo P-delta e comparou-se com os esforços de segunda ordem calculados pela majoração dos esforços de primeira ordem pelo método do coeficiente Gama-Z. Após, calculou-se os esforços internos pelos dois métodos de cálculo onde foram comparados os resultados e as variações analisadas. Verificou-se que nos cenários onde foram utilizados a majoração dos esforços de primeira ordem pelo coeficiente Gama-Z entre 1,1 e 1,3, os esforços internos calculados foram próximos ao método de cálculo complexo do processo P-Delta. Já para os resultados da utilização do coeficiente Gama Z superiores a 1,3, as variações dos esforços internos foram grandes e pode-se gerar situações que não representam a realidade da estrutura. Portanto, a utilização do coeficiente Gama Z 1,1 foi o cenário que trouxe resultados mais próximos ao método do processo P-Delta. Mesmo sendo simplificação de cálculo, a utilização do coeficiente Gama Z-1,1 traz resultados satisfatórios. [resumo fornecido pelo autor]
Keywords: Engenharia civil; Construção civil; Engenharia de estruturas